2021
DOI: 10.1002/app.50845
|View full text |Cite
|
Sign up to set email alerts
|

Tunable morphology and resistivity of ternary polymer composites of carbon black/low density polyethylene/ethylene‐vinyl acetate with carbon blacks having different surface properties

Abstract: Medium to extra‐high voltage electrical cables typically comprise a semiconductive polymer composite layer to homogenize the electromagnetic field through the cables. The semiconductive layers usually contain a high content of carbon black (CB) for reduced electrical resistivity. In this study, we found that both the morphology and resistivity of a ternary polymer composite of CB/low density polyethylene (LDPE)/ethylene‐vinyl acetate (EVA) depend on CBs used and the order of addition. Three types of CB were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…13 Currently, high-voltage XLPE cables usually use lowdensity polyethylene (LDPE)/ethylene vinyl acetate (EVA)/carbon black (CB) composites as their shielding materials. [14][15][16] Yu et al investigated the electrical conductivity and positive temperature coefficient effect (PTC) of LDPE/EVA/CB blended systems. 17 The results show that the resistivity of the blended system can be adjusted by double permeation and two-step permeation effects due to the addition of EVA, which effectively improves the processing and electrical properties of the composites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Currently, high-voltage XLPE cables usually use lowdensity polyethylene (LDPE)/ethylene vinyl acetate (EVA)/carbon black (CB) composites as their shielding materials. [14][15][16] Yu et al investigated the electrical conductivity and positive temperature coefficient effect (PTC) of LDPE/EVA/CB blended systems. 17 The results show that the resistivity of the blended system can be adjusted by double permeation and two-step permeation effects due to the addition of EVA, which effectively improves the processing and electrical properties of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, high‐voltage XLPE cables usually use low‐density polyethylene (LDPE)/ethylene vinyl acetate (EVA)/carbon black (CB) composites as their shielding materials 14–16 . Yu et al investigated the electrical conductivity and positive temperature coefficient effect (PTC) of LDPE/EVA/CB blended systems 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the higher the structure of CB the better the electrical properties of the composite. 8 Chinese scholar Yang used EVA and two types of CBs to prepare two kinds shielding materials and tested the electrical properties of the shielding materials. The results showed that when the CB concentration was the same, the shielding material with the higher structured CB had better electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of CB concentration to shielding material performance and the effect of CB type to shielding material electrical properties are more studied. [8][9][10][11][12][13][14][15] However, most of the current matrix resins for high-voltage cable shielding material are ethylene-butyl acrylate (EBA) copolymer, and there are few studies on how the type and concentration of CB affect the electrical, thermal and mechanical properties of shielding materials. Therefore, in this paper, EBA was used as the matrix resin to investigate the effect of CB type and concentration on the performance of semiconductive shielding layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation